Important Therapeutic Targets in Chronic Myelogenous Leukemia - Kantarjian, Hagop M.; Giles, Francis; Quintás-Cardama, Alfonso; Cortes, Jorge (Clinical cancer research, 2007)
Purpose: Review the state-of-art knowledge of the biology and therapy of chronic myelogenous leukemia (CML). Experimental Design: A review of the literature was undertaken to summarize current information on the pathophysiology of CML and to update data of imatinib mesylate therapy, mechanisms of resistance, and in vitro and clinical data with the new tyrosine kinase inhibitors. Results: Imatinib, which targets the ABL kinase activity of BCR-ABL, has prolonged survival in CML. Despite the efficacy of imatinib, some patients in chronic phase and more in advanced phases of CML develop resistance, frequently as a result of BCR-ABL tyrosine kinase domain mutants that impair imatinib binding but retain enzymatic activity. New tyrosine kinase inhibitors inhibit BCR-ABL more potently than imatinib and maintain activity against an array of imatinib-resistant BCR-ABL mutants. The IC 50 values of nilotinib and dasatinib are at least 10- to 100-fold lower for BCR-ABL compared with imatinib. Phase I-II trials of nilotinib and dasatinib showed high activity in imatinib-resistant CML and Philadelphia chromosome–positive ALL. Dasatinib also inhibits members of the Src family of kinases (SFKs); nilotinib does not. Whether SFKs have a critical role in imatinib resistance or BCR-ABL–mediated oncogenesis is unresolved. Agents that target signals downstream of BCR-ABL (e.g. Ras/Raf and phosphatidylinositol 3-kinase) are under investigation. Conclusions: Understanding the pathophysiology of CML and mechanisms of resistance has produced effective targeted strategies for imatinib-resistant CML.